FAKTOR KUNCI KEBERHASILAN MANAJEMEN RANTAI PASOKAN PENANGANAN BENCANA ALAM DALAM PERSPEKTIF PEMERINTAH - Poppy Laksita Rini (Jurnal Fokus Manajemen Bisnis, 2020)
Disaster supply chain management is different from the supply chain management of commercial organization because of the high level of uncertainty. The high level of uncertainty significantly affects the availability of logistic supplies that are needed by the victims of the disaster. This study discovers the key success factors of the disaster supply chain management based on the perspective of the government. The re- search specifically study the Government of the D.I. Yogyakarta that are represented by Badan Penanggulangan Bencana Daerah (BPBD). Due the fact that Yogyakarta as one of the regions that have the high risk of catastrophic nature in Indonesia. The study will be carried out in a qualitative methodology by conducting deep interview with the Representative of Logistics Department in BPBD. The results of in-depth interviews with four representative of BPBD found that there are six key success factors of disasater management supply chain management which are : (1) Quality of the TRC Team Assessment Results; (2) BPBD Coordination with Government and Non-Government; (3) Effective Rules and Regulations; (4) Character and Attitude of the Community in Dealing with Disasters; (5) BPBD Warehouse Inventory Management; (6) Management Information Systems and Data Updates.